An evaluation of the levels of 25-hydroxyvitamin D3 and bone turnover markers in professional football players and in physically inactive men - Solarz, K; Kopeć, A; Pietraszewska, J; Majda, F; Słowińska-Lisowska, M; Mędraś, M (Physiological research, 2014)
Vitamin D is synthesised in the skin during exposure to sunlight and its fundamental roles are the regulation of calcium and phosphate metabolism and bone mineralisation. The aim of our study was to evaluate serum levels of 25-hydroxyvitamin D3, PTH and bone turnover markers (P1NP, OC, beta-CTx, OC/beta-CTx) and the intake of calcium and vitamin D in Polish Professional Football League (Ekstraklasa) players and in young men with a low level of physical activity. Fifty healthy men aged 19 to 34 years were included in the study. We showed that 25(OH)D3 and P1NP levels and OC/beta-CTx were higher in the group of professional football players than in the group of physically inactive men. The daily vitamin D and calcium intake in the group of professional football players was also higher. We showed a significant relationship between 25(OH)D3 levels and body mass, body cell mass, total body water, fat-free mass, muscle mass, vitamin D and calcium intake. Optimum 25(OH)D3 levels were observed in a mere 16.7% of the football players and vitamin D deficiency was observed in the physically inactive men. The level of physical activity, body composition, calcium and vitamin D intake and the duration of exposure to sunlight may significantly affect serum levels of 25(OH)D3.
Keywords: mladý dospělý; Bone Density; Calcifediol; Humans; lidé; kalcifediol; kostní denzita; Vitamin D Deficiency; Male; sedavý životní styl; Adult; Sedentary Behavior; mužské pohlaví; remodelace kosti; pohybová aktivita; fotbal; Young Adult; dospělí; Motor Activity; nedostatek vitaminu D; Soccer; Bone Remodeling